Trapped by the Medium: Language and the Social in Relational Sociology - Bucholc, Marta (Stan Rzeczy, 2017)
This paper discusses the philosophical background and socio-theoretical affinities of Pierpaolo Donati’s relational sociology, focusing particularly on language as a missing element in relational social ontology. Following a discussion of Norbert Elias’s and Charles Wright Mills’s ideas of modernity as a counterpart to Donati’s theorizing, the paper criticizes the concept of relational society and the limitations to its applicability. The author argues that the communicational aspect of social relations calls for linguistic normativity as the basis of all normativity in a society that Margaret Archer and Donati call “morphogenic.”